International trade disputes and EU liability - Thies, Anne, 1975- (Cambridge studies in European law and policy., 2013)
"The European Union has become the respondent of several international trade disputes. This book examines the right to compensation for damage resulting from retaliatory measures imposed under the system of the World Trade Organization in disputes triggered by the EU. Anne Thies evaluates the implications of the EU's membership in the WTO for its domestic system of rights and judicial protection. Emphasising the necessity to maintain EU standards of protection independently of the external dimension of EU action, the book offers suggestions on how the current gap of protection could be filled while upholding the scope of manoeuvre of the EU institutions on the international plane. Moreover, it places the issue in its broader context of the relationship between international and EU law on the one hand, and the discretion of the EU as a global actor and standards of individual rights protection under EU law on the other"--